Assessment of the efficacy of restoring reading performance after refractive lens exchange with a trifocal intraocular lens - Naujokaitis, Tadas; Auffarth, Gerd U.; Baur, Isabella; Hassel, Oliver; Henningsen, Nikola; Reitemeyer, Emanuel; Chychko, Lizaveta; Łabuz, Grzegorz; Khoramnia, Ramin (Journal of refractive surgery, 2025)
PURPOSE: To evaluate the efficacy of refractive lens exchange (RLE) with a trifocal intraocular lens (IOL) implantation by assessing reading performance and visual acuity at near and intermediate distances. METHODS: This was a prospective interventional case series of 27 patients (54 eyes) at a university hospital who underwent a femtosecond laser-assisted RLE with Clareon PanOptix IOL (Alcon Laboratories, Inc) implantation. Visual acuity was tested before surgery and 6 months postoperatively and reading performance was evaluated using the Salzburg Reading Desk (SRD Vision) at near and intermediate distances. With a software-based simulator, the perception of halo and glare were quantified. RESULTS: The uncorrected and distance-corrected near (40 cm) and intermediate (60 cm) visual acuities improved, with the mean (+/- standard deviation) postoperative binocular uncorrected visual acuity of 0.03 +/- 0.08 logarithm of the minimum angle of resolution (logMAR) at 40 cm and-0.08 +/- 0.06 logMAR at 60 cm. The surgery also improved uncorrected reading acuities, with the postoperative binocular uncorrected reading acuity of 0.05 +/- 0.08 logMAR at 40 cm and 0.09 +/- 0.10 logMAR at 60 cm. The postoperative uncorrected reading acuity matched the preoperative reading acuity with spectacle correction for near (0.04 +/- 0.10 logMAR, P = .495). The near vision efficacy index was 0.75 +/- 0.12 for conventionally measured visual acuity and 0.99 +/- 0.35 for reading acuity. A total of 77.8% of patients reported halo and 14.8% reported glare, although none complained of bothersome photic phenomena. CONCLUSIONS: The RLE surgery effectively restored good uncorrected near and intermediate vision in terms of visual acuity and reading performance. At high luminance and contrast levels, the postoperative uncorrected reading ability matched the preoperative spectacle-corrected performance for near.
Gesehen am 12.01.2026